FORMATION OF RESEARCH COMPETENCIESOF FUTURE TEACHERS OF PRESCHOOL PEDAGOGICS AND PSYCHOLOGY - Kozak, Liudmyla (Continuing Professional Education: Theory and Practice, 2019)
In the article actuality formation of research competencies of future teachers of preschool pedagogics and psychology in preparation to innovative professional activity; it is exposed essence of concepts “research competence”, “research jurisdiction”; certainly maintenance of research jurisdictions of future teachers and condition of their forming, the forms of organization are presented scientifically research works of Master of preschool type.Established that the research work of undergraduates is one of the most important means of effective training of future teachers of preschool education and psychology to an innovative professional work, as it provides strong relationship between academic disciplines and research activities, leading to the discovery of new facts, identifying patterns, deepening and systematization of the gained knowledge. Proved that the formation of future teachers promotes research competencies: mastery undergraduates methodology and methods of pedagogical research organization and conduct of the peculiarities of pedagogical experiment, the diagnostic tools for the study of personality development of the student, the child of preschool age, level of personal self-development; familiarization with the method of the study of innovative pedagogical practices; performance of individual search and research tasks; implementation of innovative technologies in teaching vocational and educational courses; perform custom tasks during exploratory teaching practice, individual tasks aimed to optimizing the activities of educational institutions; teaching undergraduates technology preparation of reports, articles, reports and other materials on the master’s thesis process innovation aimed to research practices; organization of undergraduates participation in conferences, contests Student Research and others.